Tablet Effervescent Ekstrak Belimbing Wuluh (Averrhoa bilimbi L.) dengan variasi Kadar Pemanis Aspartam - Dewi, Rosmala; Iskandarsyah, Iskandarsyah; Octarina, Devi (Pharmaceutical Sciences and Research, 2014)
Averrhoa bilimbi is fruit that has many benefits but the usage is not optimal. That is why the aim of the research is to get formulation of effervescent granule and tablet containing dry Averrhoa bilimbi extract with modified concentration of aspartame as sweetening agent for commercial healthy drink. Granules and tablets were produced with dry method granulation with 40% of relative humidity (RH) and 25ºC of temperature. The three of formulation were qualified as effervescent granules and tablets. Favorite tests showed that no significant differences of appearances, tastes for three of effervescent granules and tablets.